JAPAN INTERNATIONAL COOPERATION AGENCY (JICA) DAN PEMBANGUNAN INFRASTRUKTUR DI INDONESIA: STUDI KASUS PEMBANGUNAN SABO DAM DI YOGYAKARTA - , Erik Vian Sukolistiono, Dra. Siti Daulah Khoiriati, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Economic and political development of the nation state to be the case that menareik for the dynamics of international politics . One issue raised was the case of the transfer of foreign aid to the group of developed countries in third world countries . One of the classic and contemporary cases to date (2013 ) is a Japanese aid in supporting development in Indonesia , which is reflected on the support of the Japan International Cooperations Agency (JICA ) in infrastructure development sabo dam disaster . One of the projects that are the focus of JICA in the development sabo dam in Indonesia is the sabo dam project Merapi . This is important because not only the Merapi volcano, located in two provinces at once , namely Yogyakarta and Central Java , but also the characteristics of the mountain is very damaging ( high explosive ) so that the role of sabo dams Merapi become so important when compared to the sabo dam projects other in Indonesia . The role of JICA in the sabo dam project Merapi was not solely oriented on purely technical factors , but also politically . Sabo dam Merapi turned out to be part of the policy / foreign policy of Japan . In addition , the construction of sabo dam Merapi also be part of the interaction of transnational actors as the Japanese government through JICA continuously seeks to support the development of technical support , budget , and human resource development . From the political aspect of the implementation of JICA programs in development sabod am Merapi turned out to involve all actors of society presidents to dis ekitar Indonesia Merapi . Then each implementation can run a variety of synergistic relationship , although not yet fully effective . The description of the above descriptions are complete will be described in this research